Analisis kebijakan politik hukum pemerintah Kota Cilegon atas peningkatan kesejahteraan rakyat Tahun 2010-2015 - Fatoni, Malik Fatoni; Surachman, Surachman (Fakultas Ekonomi, UIN Maliki Malang, 2019)
The study aims to determine the extent of policy effectiveness that comes from the polarization of executive and legislative relations can affect the welfare of the people of Cilegon city. To get the achievement and progress for the improvement of people's welfare, it is necessary to analyze policy concerning politic and law policy to be reviewed to document, observation and interview. thereby facilitating an analytical, constructive, explorative and documentative study. this is often called the data triangulation method. method is merging various methods of data collection. The research was conducted in Cilegon city using Qualitative research with Grounded Theory approach. data collection techniques is by data triangulation method. this is often called a method that combines various methods of data collection, such as observation, interviews and documentation. of this research is expected to increase the productivity of policies and efficiency of planning programs in the field of politics and law formulated by the regional government of Cilegon city can improve people's welfare. The results achieved from this research is the political policy of law conducted by the City Government Cilegon can encourage the improvement of the welfare of the people, this can be seen from the legislation product endorsed by Parliament Cilegon in quality and quantity is very good so that the product can be implemented properly by executives and provide juridical strength for the City Government Cilegon in improving economic development, as seen from indicators of improving the welfare of the people themselves. The political policy of law that is processed and in synergy between the existing government institutions in Cilegon City, indicates the strong and strong commitment of these institutions to encourage and improve the welfare of a just and equitable people.